Brazilian Bare Nouns in Comparatives: Experimental Evidence for Non-Contextual Dependency - Beviláqua, Kayron; Pires de Oliveira, Roberta (Revista Letras, 2017)
This is an empirical investigation into the volume interpretation attested for the Bare Singular (BS) in Brazilian Portuguese (BrP) in previous studies (e.g.: Beviláqua e Pires de Oliveira, 2014). The issue is whether it is contextually dependent, as argued by Lima & Gomes (2016) and Beviláqua et al (2016). The results indicate that besides a cardinal reading, the volume interpretation is significantly associated with the BS, independently of the context. The BP is normally compared by the number of individuals, however the BP accepted some volume judgments in the biased context. We conclude that the results about the BS shows that its volume reading is not contextually dependent, contradicting Lima & Gomes (2016) and Beviláqua et al.’s (2016) prediction. We criticize Rothstein & Pires de Oliveira’s (2016) explanation for the behavior of the BS; the authors treat it as flexible nouns in English (Rothstein & Pires de Oliveira (2016)). However, English flexible nouns in a mass context do not allow the cardinal reading. We suggest that the BS is under-determined because it denotes the kind.